The Consistency Of Intrasubject Valence And Instrumentality Measures: A Methodological Consideration - Muchinsky, Paul M. (Academy of Management Journal, 1977)
The article discusses the results of a study pertaining to the consistency of intrasubject valence and instrumentality measures. Undergraduate students at a large U.S. midwestern university were evaluated to determine the outcomes students typically derive from taking courses. The study indicates that students perceived the attractiveness of the same outcomes to differ across the various courses they took. The outcome respect from peers frequently received a higher valence in upper division courses than in lower division courses.